PSYCHOMETRIC PROPERTIES OF ROMANIAN VERSION OF WHO-5 WELL-BEING INDEX IN DENTAL STUDENTS - Cristina Teodora Preoteasa; Elena Preoteasa (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study: To evaluate psychometric properties of Romanian version of WHO-5 Well-Being Index, as a brief well-being scale and as a depression screening questionnaire, in dental students. Material and methods: This cross-sectional study was implemented on second and third dental students. Data was collected during winter semester evaluation period of 2014-2015 academic year. Psychological well-being was assessed by WHO-Five Well-being Index (WHO-5) and Major Depression Inventory (MDI). Results: The target population included 317 second and third year dental students, overall response rate being 87%. The mean WHO-5 score was 12.67, and 59.3% of dental students were recommended to be tested for depression. The mean MDI score was 16.20, and 35.8% of students were likely to present depression. Female students and those of Romanian nationality registered lower levels of psychological well-being. The Cronbach's alpha coefficient for the Romanian version of WHO-5 total scale was 0.882. The average inter-item correlation was coefficient 0.599, with individual correlations ranging from 0.519 to 0.724. Analysing convergent validity a significant association was identified between WHO-5 and MDI (r=-0.640; p<0.001; n=264), and also between WHO-5 and selfreported perception about life as a whole (r=-0.358; p=<0.001; n=262). The area under the curve (AUC) was 0.822; 95% CI: 0.772-0.872; p<0.001. For the cut-off value of WHO-5 score of ≤12, respectively WHO-5 score ≤12 or choosing answers with the minimum scores, the sensitivity was 87%, respectively 89% in detecting depression. Conclusions: The Romanian version of WHO-5 was found to have good psychometric properties as well-being scale and as a screening instrument in detecting depression in dental students. It presented a satisfactory sensitivity with a cut-off of ≤12 in detecting depression in dental students.